Comparison of cathodic delamination of poly(n‐alkyl methacrylates) on iron. Issue 12 (31st January 2017) - Mondragón Ochoa, J. S.; Altin, A.; Erbe, A.
Abstract : Cathodic delamination is measured on iron surfaces covered with different poly(n‐alky methacrylates), where the alkyl is an n‐C n H2 n  + 1 ( n  = 1, 4, 18) group. The polymers are prepared by free radical polymerization in solution and spin coated individually on iron. The materials were characterized by infrared (IR) spectroscopy, ellipsometry, and contact angle measurements. Barrier properties in potassium chloride were obtained by electrochemical impedance spectroscopy (EIS). Artificial defects in the polymer model coatings were exposed to 1 M potassium chloride as corrosive medium, and cathodic delamination was measured by a scanning Kelvin probe. The surface wettability decreases as the size of the pending alkyl group in the backbone increases. The same chemical feature shows also an effect on the cathodic delamination and on the electrochemical impedance results. Delamination is roughly twice as fast when n  = 1, compared to n  = 4 and n  = 18. The difference in delamination rate between the latter two polymers is small. Abstract : Cathodic delamination of poly(n‐alky metacrylate)s‐covered iron is evaluated. It is found that the n‐alkyl size in the side chains of the polymers influences strongly the barrier properties of the coatings, the surface wettability as well as the delamination rate of the polymers on the metal surface in presence of a chloride‐containing corrosive medium.